Associations of public transport accessibility with walking, obesity, metabolic syndrome and diabetes. Issue 2 (June 2016) - Barr, Alison; Bentley, Rebecca; Simpson, Julie A.; Scheurer, Jan; Owen, Neville; Dunstan, David; Thornton, Lukar; Krnjacki, Lauren; Kavanagh, Anne
Abstract: Objective: To examine associations of public transport system accessibility with walking, obesity, metabolic syndrome and diabetes/impaired glucose regulation. Methods: Associations of public transport accessibility with self-reported walking for transport or recreation and measured biomarkers of chronic disease risk were estimated in 5241 adult residents of 42 randomly selected areas in Australia in 2004/05, drawn from the second wave of a population-based cohort study (AusDiab). Public transport accessibility was objectively measured using an adaptation of the Public Transport Accessibility Levels (PTAL) methodology, comprising both GIS derived spatial and temporal accessibility measures. Logistic regression models were adjusted for individual and environmental level covariates and clustering within areas. Results: Above median public transport accessibility was positively associated with a walking time of more than the median 90 min per week (OR=1.28, 95%CI 1.03, 1.60) and walking above the recommended 150 min per week (OR=1.35, 95%CI 1.11, 1.63). There were no associations of public transport accessibility with obesity (OR=1.05, 95%CI 0.85, 1.30), the metabolic syndrome (OR=1.09, 95%CI 0.91, 1.31) nor diabetes/impaired glucose regulation (OR=1.11, 95%CI 0.94, 1.30). Findings were similar for a subgroup reporting no vigorous recreational physical activity. Conclusions: In this Australian sample, public transport accessibility was positively associated with walking at recommended levels, including for people who are not otherwise vigorously active. Significance: Walking is crucial for increasing physical activity levels and population health, as well as maximising public transport system efficiency. Building evidence on public transport accessibility and walking will enable governments to exploit this important synergy. Highlights: Study of public transport access and markers of health risk in Australian adults. Public transport access measure includes spatial and temporal dimensions. Public transport access is associated with weekly walking at recommended levels. Public transport access is not associated with obesity or cardio-metabolic disease. Findings do not vary by participation in vigorous recreational physical activity.